2007
DOI: 10.1021/jp067226u
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Binary Mixture Adsorption of Carbon Dioxide and Methane in Carbon Nanotubes:  Temperature, Pressure, and Pore Size Effects

Abstract: Grand canonical Monte Carlo (GCMC) simulations were performed to investigate the adsorption behavior of an equimolar CO2/CH4 mixture in carbon nanotubes (CNTs). Five CNTs [(6, 6), (7, 7), (8, 8), (9, 9), and (10, 10)] with diameters varying from 0.678 to 1.356 nm, seven temperatures (283, 293, 303, 313, 323, 333, 343 K), and seven pressures (1, 5, 10, 15, 20, 25, 30 MPa) were chosen to investigate the effect of temperature, pressure, and pore size on the adsorption behavior. The results show that the CNTs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
129
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 39 publications
7
129
2
Order By: Relevance
“…preferential adsorption towards CO 2 ) significantly increased (Kowalczyk et al 2012). The selectivities in the activated carbon is lower than that obtained on carbon nanotubes (Huang et al 2007), but close to the selectivity in C168 models (Babarao et al 2007). Finally in the coals with large clusters, greater selectivity is observed at low pressures, which tends to decrease with increasing pressure.…”
Section: Pure Components Isothermsmentioning
confidence: 66%
“…preferential adsorption towards CO 2 ) significantly increased (Kowalczyk et al 2012). The selectivities in the activated carbon is lower than that obtained on carbon nanotubes (Huang et al 2007), but close to the selectivity in C168 models (Babarao et al 2007). Finally in the coals with large clusters, greater selectivity is observed at low pressures, which tends to decrease with increasing pressure.…”
Section: Pure Components Isothermsmentioning
confidence: 66%
“…2 Understanding the molecular phenomena related to adsorption and transport of CO2-hydrocarbon mixtures in the sub-surface is therefore necessary in order to optimize both CO2 storage capacity, as well as oil and gas production. Despite the vast literature on binary CO2 and CH4 mixtures, [3][4][5] few studies focused on adsorption and dynamics of CO2 mixtures with more economically attractive, higher molecular weight hydrocarbons under confinement. 6,7 We previously conducted extensive molecular dynamics (MD) simulations to study propane adsorption, structure and diffusion in slit-shaped silica pores at sub-, near-, and super-critical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…20,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Most of these simulation studies consider classical force fields, but ab initio calculations have also been reported. 19,27,42 The capacity of carbon nanotubes to adsorb pure CO 2 has been tested by computer simulations in isolated 19 and arrays of parallel SWCNTs, 20 as well as isolated 36 and parallel double-walled carbon nanotube bundles.…”
Section: Introductionmentioning
confidence: 99%
“…19,27,42 The capacity of carbon nanotubes to adsorb pure CO 2 has been tested by computer simulations in isolated 19 and arrays of parallel SWCNTs, 20 as well as isolated 36 and parallel double-walled carbon nanotube bundles. 38,40 On the other hand, CO 2 separation by carbon nanotubes from mixtures has been studied in CO 2 -CH 4 mixtures, 30,39 in presence of water 37 or in CO 2 -N 2 mixtures. 33 This latter study, relevant for CO 2 capture from flue gases, studied the effect of pressure, temperature, and bulk gas composition on the CO 2 adsorption in SWCNTs with diameters between 8 and 10 Å.…”
Section: Introductionmentioning
confidence: 99%